2004
DOI: 10.1111/j.1468-3083.2004.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care in patients with psoriasis: an initial clinical study of an international disease management programme

Abstract: The disease management programme was found to be a useful tool in the management of psoriasis, providing patients with relief from the burden of psoriasis in everyday life. A full-scale evaluation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 15 publications
2
56
0
Order By: Relevance
“…Twenty-four of them were retained after filtering duplicates. After reading the remaining articles in full, four were excluded because their intervention was mainly non-educational (10)(11)(12)(13), five on the grounds of absence of a QoL outcome parameter (14)(15)(16)(17)(18), and a further five because they turned out to be non-randomised studies (19)(20)(21)(22)(23). Searching the references used in a systematic review on atopic dermatitis by Errser et al (24) yielded one additional publication (25).…”
Section: Literature Searchmentioning
confidence: 98%
“…Twenty-four of them were retained after filtering duplicates. After reading the remaining articles in full, four were excluded because their intervention was mainly non-educational (10)(11)(12)(13), five on the grounds of absence of a QoL outcome parameter (14)(15)(16)(17)(18), and a further five because they turned out to be non-randomised studies (19)(20)(21)(22)(23). Searching the references used in a systematic review on atopic dermatitis by Errser et al (24) yielded one additional publication (25).…”
Section: Literature Searchmentioning
confidence: 98%
“…The management of psoriasis depends upon the cultural habits of each country, the health insurance system, the number of patients and physician demography [19,56,57,58,59,60]. In the French national context, the vast majority of patients stated that they had consulted a medical practitioner for their disease, and about 40% had seen a dermatologist, which represents a significant economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Hopefully, less experienced dermatologists refer patients in need of these conventional but potentially toxic therapies to more experienced colleagues instead of denying patients these treatments. Although it may be less convenient for patients from a practical perspective, a recent European study suggested that the creation of subspecialized care centres for psoriasis increased satisfaction with care [21]. …”
Section: Discussionmentioning
confidence: 99%